Daily outpatient intravenous antibiotic therapy for the management of paediatric periorbital cellulitis, a retrospective case series. (6th February 2019) - Tritt, Ashley; Kay‐Rivest, Emily; Paradis, Tiffany; Duval, Melanie
Abstract : Objective: To evaluate whether outpatient treatment of periorbital cellulitis with daily administration of intravenous antibiotics and physician evaluation is an effective and safe alternative to admission. Design: A retrospective chart review study of paediatric patients treated on an outpatient basis for periorbital cellulitis at a tertiary children's hospital between 2013 and 2015 was performed. Children were assessed day by a paediatrician to monitor for resolution of symptoms or complications. Setting: The Montreal Children's hospital, a tertiary care centre. Participants: Children diagnosed with an uncomplicated periorbital cellulitis secondary to an acute sinusitis or upper respiratory tract infection. Main outcome measures: The number of days of intravenous antibiotics, complications or need for subsequent admission. Complications were defined as formation of an abscess or phlegmon confirmed on computerised tomography scan, worsening or recurrent persistent cellulitis, failure to improve on intravenous antibiotics, and intracranial complications. Results: Sixty‐six children with a diagnosis of uncomplicated periorbital cellulitis secondary to sinusitis who received intravenous antibiotics via medical day hospital and who fit the inclusion criteria were identified. The mean duration of intravenous antibiotic therapy was 4.1 days. All children received ceftriaxone, with one patient also receiving cefuroxime. Two of 66 patients developed complications; one patient required admission for failure to improve/subperiosteal phlegmon and later underwent functional endoscopic sinus surgery, and one patient developed an eyelid abscess that did not require admission. No patients developed severe neurological or visual deficits. Conclusions: Outpatient intravenous therapy with daily reassessment by a physician may be a safe alternative to admission in select cases of periorbital cellulitis without systemic signs of illness.